Market Economy Status in European Union Antidumping Policy against China - Skrzypczyńska , Joanna (Studia Oeconomica Posnaniensia, 2018)
Anti-dumping procedures allow competing with price competition from China and are an effective tool of trade protectionism. Under Section 15 of the Chinese WTO Accession Protocol, China could be treated as a non-market economy (NME) in anti-dumping proceedings to the end of 2016. Finally, the European Commission has to propose a new method for calculating dumping margins for imports from countries with market distortions and a government's dominant influence on the economy. The main goal of this paper is to analyse the antidumping procedure of the European Union and examine the Market Economy status for China.